A cross sectional study of the prevalence of hypertension and associated risk factors in coastal Andhra Pradesh - Koduru, Gopalakrishna; Subrahmanya Sarma, Venkata R. S.; Palaparthi, Raghuram; Sarada Srinivas, Chowdary Parvethaneni; Koduru, Purnachandrarao; Ghanta, Somasekhar; Manne, Boochibabu; Maganti, Prasad; Yendapalli, Sasidhar (International Journal Of Community Medicine And Public Health, 2019)
Background: Hypertension (HTN) accounts for 9.4 million deaths worldwide every year. A rise in HTN is projected by the global burden of HTN 2005 study, it portrays a grim picture. Community level data for hypertension is scarce in Andhra Pradesh. A cross sectional study was conducted to know the prevalence of hypertension in Vijayawada. Methods: 1009 apparently healthy adults visiting the hospital accompanying patients in outpatient department were screened for hypertension by blood pressure recording. All measurements were obtained by automated blood pressure measuring (AOBPM) systems. Results: Of the total population screened, hypertension accounted for 42.5% (n=429). A multivariate analysis showed that hypertension is more common in age group >50 years [odds ratio (OR)=3.004, 95% confidence interval CI being=2.2707-3.9645], in diabetics (OR=2.9091, 95% CI=2.0595-4.1092), in males (odds ratio=1.3223, 95% CI=1.0214-1.7118) and in smokers (OR=1.7442, 95% CI=1.0469-2.9059). A linear positive association was found between obesity and hypertension. No significant association was found between hypertension and alcohol intake. This study also showed that awareness was present in only 44% and 37% had hypertension under control of known hypertensive subjects. Conclusions: This is the first cross sectional study done with AOBPM. Our study finds that hypertension is an important public health burden in coastal Andhra Pradesh with low awareness, treatment, and control. It implies that strategies need to be developed to improve effective primary care management of hypertension.